2004
DOI: 10.1016/j.jpainsymman.2003.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Symptom burden in the last week of life

Abstract: In order to investigate symptom burden in the last week of life, we conducted after-death interviews with close relatives of deceased older persons from a population-based sample of older people in The Netherlands (n=270). Results show that fatigue, pain, and shortness of breath were common (83%, 48% and 50%, respectively). Other symptoms were confusion (36%), anxiety (31%), depression (28%), and nausea and/or vomiting (25%). Cancer patients and patients with chronic obstructive pulmonary disease were clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 18 publications
0
62
0
10
Order By: Relevance
“…These symptoms have been found as being typical for the last weeks of life in other studies too [18,19]. Six percent of the patients who died during the study period could not be included in the study because they were physically or mentally unable to give informed consent.…”
Section: Discussionmentioning
confidence: 74%
“…These symptoms have been found as being typical for the last weeks of life in other studies too [18,19]. Six percent of the patients who died during the study period could not be included in the study because they were physically or mentally unable to give informed consent.…”
Section: Discussionmentioning
confidence: 74%
“…These reports support the idea that this tumor animal model may present behavioral depression. Depression is one of the major symptoms commonly found in cancer patients, and reported to worsen survival of the patients (Goodwin et al, 2004;Klinkenberg et al, 2004). However, the brain mechanism by which cancer induces depression in the patients is not known.…”
Section: R Esults and Discussion 5-htt Expressionmentioning
confidence: 99%
“…It has been reported that serum concentrations of tryptophan, 5-HT precursor, are significantly decreased in cancer patients (Brown et al, 1989;1991), and that this decrease correlates with depressive symptoms in cancer patients undergoing cytokine therapy (Capuron et al, 2002). Depression is one of the major symptoms commonly found in cancer patients, and reported to worsen survival of the patients (Goodwin et al, 2004;Klinkenberg et al, 2004). However, the mechanism by which cancer induces depression in the patients is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this study a larger proportion of the patients appeared to be experiencing the most reported refractory symptoms, possibly providing a reflection of the symptom burden in the last week of life. 27 Euthanasia is fundamentally different from palliative sedation. Dutch law defines euthanasia as the ending of life of a patient, at their explicit request due to unbearable and lasting suffering, performed by a physician who fulfils strictly-defined requirements.…”
Section: Strengths and Limitationsmentioning
confidence: 99%